Cerebellar volume as an imaging marker of development in infants with tuberous sclerosis complex. (24th April 2018) - Srivastava, Siddharth; Prohl, Anna K.; Scherrer, Benoit; Kapur, Kush; Krueger, Darcy A.; Warfield, Simon K.; Sahin, Mustafa
Abstract : Objective: In this cohort analysis, we studied 1-year-old infants with tuberous sclerosis complex (TSC), correlating volumes of cerebellar structures with neurodevelopmental measures. Methods: We analyzed data from a prospective biomarker study in infants with TSC (ClinicalTrials.gov NCT01780441). We included participants aged 12 months with an identified mutation of TSC1 or TSC2 . Using MRI segmentation performed with the PSTAPLE algorithm, we measured relative volumes (structure volume divided by intracranial contents volume) of the following structures: right/left cerebellar white matter, right/left cerebellar exterior, vermal lobules I–V, vermal lobules VI–VII, and vermal lobules VIII–X. We correlated relative volumes to Mullen Scales of Early Learning (MSEL) scores. Results: There were 70 participants (mean age 1.03 [0.11] years): n = 11 had a TSC1 mutation; n = 59 had a TSC2 mutation. For patients with TSC2 mutation, for every percentage increase in total cerebellar volume, there was an approximate 10-point increase in MSEL composite score (β = 10.47 [95% confidence interval 5.67, 15.27], p < 0.001). For patients with TSC1 mutation, the relationship between cerebellar volume and MSEL composite score was not statistically significant (β = −10.88 [95% confidence interval −22.16, 0.41], p = 0.06). For patients with TSC2 mutation, there were positive slopes when regressing expressive language and visual reception skills with volumes of nearly all cerebellar structures ( p ⩽ 0.29); there were also positive slopes when regressing receptive language skills, gross motor skills, and fine motor skills with volumes of cerebellar right/left exterior ( p ⩽ 0.014). Conclusions: Cerebellar volume loss—perhaps reflecting Purkinje cell degeneration—may predict neurodevelopmental severity in patients with TSC2 mutations.